2015
DOI: 10.1177/0284185114532081
|View full text |Cite
|
Sign up to set email alerts
|

Do mammographic tumor features in breast cancer relate to breast density and invasiveness, tumor size, and axillary lymph node involvement?

Abstract: Background Breast density and mammographic tumor features of breast cancer may carry prognostic information. The potential benefit of using the combined information obtained from breast density, mammographic tumor features, and pathological tumor characteristics has not been extensively studied. Purpose To investigate how mammographic tumor features relate to breast density and pathological tumor characteristics. Material and Methods This retrospective study was carried out within the Malmö Diet and Cancer Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Early detection and characterization are essential to ensure optimal treatment. On mammography, the best technique for screening, certain findings (e.g., certain types of calcifications, spiculated masses, or architectural distortion) suggest malignancy and can even be considered markers of poor prognosis [1,2]. However, findings among tumors vary, and few findings are specific for malignant or premalignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection and characterization are essential to ensure optimal treatment. On mammography, the best technique for screening, certain findings (e.g., certain types of calcifications, spiculated masses, or architectural distortion) suggest malignancy and can even be considered markers of poor prognosis [1,2]. However, findings among tumors vary, and few findings are specific for malignant or premalignant lesions.…”
Section: Introductionmentioning
confidence: 99%
“…ESR1 mutations (Toy et al, 2013)), or other prognostic factors such as appearance (e.g. spiculated appearances (Sartor et al, 2015)) have yet to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Mammographic techniques and improved image analysis have revealed that a breast cancer can exhibit different mammographic appearances, such as spiculations. Mammographic spiculated tumors possess a star-like appearance, which is an indicator of invasiveness linked to cancer infiltration and fibrotic growth around the tumor (Sartor et al, 2015;Alexander et al, 2006). On the molecular level, spiculated tumors have been shown to be enriched in ER and PgR positive tumor group, often comprised within the Luminal A molecular subtype, and have been linked to better prognosis when compared to well-defined and microcalcified masses (Evans et al, 2006;Taneja et al, 2008;Bullier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Breast density was graded (fat involuted/moderately dense/dense) in the original radiology report of the breast cancer diagnostic mammogram and retrospectively retrieved for research purposes ( 6 , 25 27 ). The classification can be regarded as a modified Breast Imaging Reporting and Data System (BI-RADS) 4th Ed density categorization.…”
Section: Methodsmentioning
confidence: 99%